Raman spectra of impact zircons in the Jarva-varaka layered massif (the Monchegorsk ore region, the Kola Peninsula) - Kaulina T. V.; Nerovich L. I.; Bocharov V. N.; Lyalina L. M.; Il'chenko V. L.; Kunakkuzin E. L.; Kasatkin I. A. (Vestnik MGTU, 2017)
Zircon crystals from granophyre norites of the Jarva-varaka massif of the Monchegorsk ore region (the Kola Peninsula) have been studied by means of back-scattered electron (BSE) imaging and Raman spectroscopy. The Jarva-varaka massif according to geological and geochemical data has been compared with the Sudbury structure, for which an impact origin is assumed. Zircon study is stipulated by zircon ability to keep signs of shock metamorphism even under granulite-facies conditions, thus it can be used for identification of ancient impact structures. BSE images reveal complicated internal texture – darker central domains (cores) and light rims without texture. Mineral inclusions in zircon are represented by sillimanite and plagioclase which indicates that the studied zircon grains were inherited from the host aluminous gneisses. Zircon crystals show variation of Raman spectra from the core of crystals with typical zircon Raman pattern to complete absence of spectral bands in the marginal parts and rims. Mineral inclusions in zircon rims also have no Raman spectra. Such patterns may be associated with the transformation of crystalline zircon (and mineral inclusions in it) to diaplectic glass under the influence of shock metamorphism, core domains were screened by rims and thus preserved their structure. The received data suggest the participation of the meteorite impact in the formation of the Jarva-varaka massif that requires further investigation.